Trends and Patterns of Patent in Agriculture and Allied Sector (Journal of Intellectual Property Rights (JIPR), 2023)
The present study addresses a knowledge gap by examining global and domestic patent trends in the agriculture sector, with a focus on leading agriculture patenting countries like India, China, and North America. The analysis, spanning from 1990 to 2022 and covering 37 leading agricultural countries, reveals a significant increase in global patent filings across diverse categories, even in the post-pandemic era. Southeast Asia, led by China, emerges as the primary region for agricultural patents globally, followed by North America. China exhibits substantial growth and becomes the leading country in patent filings, while the USA experiences a decline in 2022. India's representation in agricultural patents consistently declines, and sector-specific analysis underscores the importance of chemical compounds and fertilizers, animal husbandry, machinery and implements, horticulture, and new plants in patent filings. The slow progress in agricultural patenting in India highlights the need for a greater focus on technological advancements, research and development investment, protection of agricultural innovations, reduced reliance on imported technology and innovations, and enhanced collaboration. To address these challenges, it is crucial to prioritize agricultural research and development, incentivize innovation through intellectual property protection, and increase investment in research and development, and foster collaboration between the public and private sectors.